Ox-eye window - Ghosh, Ayan (Jio Institute, 2023)
An important design element Frederick W. Stevens borrowed from Venetian Gothic architecture was the use of a flower-shaped oeil-de-boeuf (ox-eye window in English), which let in natural light during the day. Though strictly not a window, because it was covered in stained glass, this circular opening is typically placed in a roof slope as a dormer, or above a door or pair of windows (as seen here).